PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA RSU BHAKTI RAHAYU AMBON - Yani Talakua; Saiful Anas; Muhammad Aqil (Sekolah Tinggi Pariwisata Mataram, 2020)
This research attempts to test the influence of work dicipline on the performance of an employe at public hospytals bhakti rahayu ambon. The hypothesis of this research is work dicipline influence the performence of an employe at public hospitals bhakti rahayu ambon.Research methodology used in writing this is the quantitative study by reserach survey . respondents in this research are employes hospytal bhakti rahayu ambon 70 people. Sample technique used is purposive sampling. Analysis of data used is descriptive statistical techniques and statistical technique iferensial of regression analysis sample spss mixed use. This research conducted in public hospytal bhakti rahayu ambon.Data obtained by the use of research instruments in the form of a questionnaire with likert scale cosisting of 14 items of statement of the variabel disipline of work and 16 items of statement for the variabels of employe performance. The result of reckoning validty and realibilitas acquired item on the variabels of divcipline of work and employee performace valid and it’s reliabel. Testing requirements analysis was done using a test of normality, a result of calculation showed that of lab data distribution normal.Reserach explained that the working performance of employees to influence significantly to hospytal bhakti rahayu ambon. It is proven by the test hypotheses of the probability of significan (0.000< 0.05) with the value of t count > of t a table ( 4.511> 2.002).